The detailed morphological formation based on geological investigation in Somawangi and surrounding areas, Mandiraja District, Banjarnegara Regency, Central Java - Qur'an, Mudrik Infithor Nurul; Siswandi, Siswandi; Gibran, Akhmad Khalil (Journal of Earth and Marine Technology (JEMT), 2022)
Geological mapping is an activity to be able to know the geological conditions of a field. Somawangi Village and its surroundings have a geological history depicting the history of the past that continues until now. This location is located in Mandiraja District, Banjarnegara Regency with a morphology consisting of rock outcrops that record past history which can be used as learning media for the field of geological science. This study aims to determine the geological conditions and resource potential as well as geological disasters at the research site. From the results of the study, it can be concluded that the Geomorphology of the research area can be divided into 3 geomorphological units, namely the Sloping Structural Hills Unit (S3), Structural Sloping Lowland Unit (S1), and Volcano Denudational Hills Unit (V14) with the composition The stratigraphy of the study area is divided into 5 rock units, from the oldest to the youngest, the Somawangi Volcanic Breccia Unit, the Sandstone Unit, the Andesite Lava Unit, the Tuff Rock Unit, and the Kaliwungu Volcanic Breccia Unit. The geological structure of the research area is the Left Fault which is found along the rivers and hills in the eastern area of the research location with an emphasis on northeast-southwest. And the geological potential of the research area can be divided into 2, namely positive potential such as mining of sand and rocks around the river, the use of red soil as a ceramic and brick material, the use of andesite lava which has the potential to mine minerals, and the presence of mineralization alteration in the research area. While the negative potential is the potential for land movement or landslides